PENGARUH KECERDASAN SPIRITUAL TERHADAP PRESTASI BELAJAR MAHASISWA JURUSAN EKONOMI SYARIAH BERDASARKAN PRESPEKTIF GENDER - Pakkawaru, Irham (Musawa: Journal for Gender Studies, 2018)
This research aims to determine influence of spiritual intelligence on students achievement and differences in learning achievement between male and female in sharia economics students at Palu. The method used in this research is purposive sampling. The sample is 100 students based on criteria. Data analysis includes: normality test, simple regression analysis and T-test. The results of this research indicate that spiritual intelligent had a significant influence on student achievement in sharia economics student at Palu and there are differences in learning achievement between male and female in sharia economics students at Palu.